Eye Movement Desensitization and Reprocessing in adolescents with autism; Efficacy on ASD symptoms and stress - Leuning, Esther Marion; van den Berk-Smeekens, Iris; van Dongen-Boomsma, Martine; Staal, Wouter G. (Frontiers in Psychiatry, 2023)
Introduction Eye Movement Desensitization and Reprocessing (EMDR) is a well-established and thoroughly researched treatment method for posttraumatic stress symptoms. When patients with an autism spectrum disorder (ASD) are treated with EMDR for their Posttraumatic Stress Disorder (PTSD), they sometimes report a decrease in the core symptoms of ASD. This explorative pre-post-follow up design study is designed to investigate whether EMDR with a focus on daily experienced stress, is effective in reducing ASD symptoms and stress in adolescents with ASD. Methods Twenty-one adolescents with ASD (age 12 to 19) were treated with ten sessions EMDR, focusing on events of daily experienced stress. Results No significant decrease of ASD symptoms was found on the total score of the Social Responsiveness Scale (SRS) as reported by caregivers from baseline to end measurement. However, there was a significant decrease on total caregivers SRS score comparing the baseline to the follow-up measurement. On two subscales, Social Awareness and Social Communication, a significant decrease was found from baseline to follow-up. On the subscales Social Motivation and Restricted Interests and Repetitive Behavior, no significant effects were found. On pre- and posttest scores of total ASD symptoms measured by the Autism Diagnostic Observation Schedule (ADOS-2), no significant effects were found. On the contrary, scores on self-reported Perceived Stress Scale (PSS) showed a significant decrease from baseline to follow-up. Also, 52% of adolescents showed a significant improvement of global clinical functioning at endpoint measurement on the Clinical Global Impression Improvement, rated by an independent child psychiatrist. Discussion In sum, these results of this uncontrolled study suggest a partial effect of EMDR in adolescents with ASD on ASD symptoms, rated by their caregivers. In addition, the results of this study show that EMDR treatment on daily experienced stress significantly reduce perceived stress as reported by the participants, and improves global clinical functioning. The results also suggest a ‘sleeper effect’, since no significant effects were found between baseline- and post- treatment measurements, but only between baseline- and follow up three months after the treatment. This finding is in line with other studies investigating psychotherapeutic effects in ASD. Implications for clinical practice and suggestions for future research are discussed.